Neutron Reflectometry to Measure In Situ Li Permeation through Ultrathin Silicon Layers and Interfaces. Issue 13 (5th September 2015) - Hüger, Erwin; Stahn, Jochen; Schmidt, Harald
Abstract : High-intensity specular neutron reflectometry was used to measure atomic transport processes in the solid state in-situ. As a model system, Li transport through ultrathin amorphous silicon layers (5 nm) and adjacent lithium silicate interfaces relevant for battery applications is studied. For the experiments a multilayer structure consisting of five [Si/ nat LiNbO3 /Si/ 6 LiNbO3 ] units was investigated, which was produced by ion beam sputtering. LiNbO3 is solely used as a tracer reservoir. Thin lithium silicate layers are formed at Si/LiNbO3 interfaces during sputtering. Two types of Bragg peaks are detectable in the neutron reflectivity pattern. One originates from the double layer periodicity introduced by the LiNbO3 /Si chemical contrast, the other from the four-layer periodicity introduced by the Li isotope contrast of the nat LiNbO3 and 6 LiNbO3 layers. If the multilayer arrangement is annealed at 240°C, Li diffusion through the silicon layer between the two isotope reservoirs is induced and only the Bragg peak due to Li isotope contrast variation is reduced, while the peak due to chemical contrast variation remains constant. High-intensity specular neutron reflectometry allows to record reflectivity patterns within some minutes, which is the base for continuous in-situ measurements during annealing. Simulation tools allow to derive the Li permeability (diffusivity x solubility) in silicon.